2023
DOI: 10.1039/d3fo01583a
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics reveal the cognitive improvement effects of Acer truncatum Bunge seed oil on hypoxic–ischemic encephalopathy rats

Abstract: Hypoxic-ischemic encephalopathy (HIE) is one of the leading causes of acute neonatal death and chronic neurological damage, and severe HIE can have secondary sequelae such as cognitive impairment and cerebral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…1a ), which has been reported in the literature as a possible cause of impaired lateral branch circulation 61 , 62 . In addition, in our previous study, we reported the results of HE staining and metabolic analysis in sham surgery rats, which also confirm the success of HIE model 63 . Due to the limited availability of samples, we are unable to perform comprehensive validation procedures for numerous biomarkers, including genes expression and lipids calculation, after transcriptomic and lipidomic assays.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…1a ), which has been reported in the literature as a possible cause of impaired lateral branch circulation 61 , 62 . In addition, in our previous study, we reported the results of HE staining and metabolic analysis in sham surgery rats, which also confirm the success of HIE model 63 . Due to the limited availability of samples, we are unable to perform comprehensive validation procedures for numerous biomarkers, including genes expression and lipids calculation, after transcriptomic and lipidomic assays.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we collected separately all remaining rat brain tissue from each of the two groups for histological evaluation ( n = 6), lipidomics ( n = 8), and transcriptomic studies ( n = 13). Especially, before the ASO intervention, we conducted a detailed examination and comparison of the Sham group ( n = 8) and the Model group ( n = 8), which was consistent with our previous study 63 . All samples were stored at −80 °C before use.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…9 ATSO has been demonstrated to prevent and ameliorate various neurological diseases such as experimental allergic encephalomyelitis, Parkinson's disease, cognitive impairment, adrenoleukodystrophy and hypoxic-ischemic encephalopathy. 10–17 Improvement of mitochondrial function and promotion of myelin regeneration are considered to be the main mechanisms of ATSO in ameliorating neurological diseases. Although these findings suggested that ATSO may also be beneficial for chemotherapy-induced demyelination, important questions regarding its cytological basis and molecular mechanisms remain to be answered.…”
Section: Introductionmentioning
confidence: 99%